History becoming and development of Institute of informative safety of radio electronics and telecommunications (radiotechnical faculty) of the Odessa national polytechnic university - Bondar, V. I.; Suhoterina, L. I.; Yampolskyi, Yu. S. (History of science and technology, 2015)
In the article history is illuminated becoming and development of institute of informative safety of radio electronics and telecommunications (radiotechnical faculty) of the Odesa national polytechnic university.